Wood anatomy of some trees with diffuse- and ring-porous wood: Some functional and ecological interpretations - LO GULLO, M A; Salleo, S (Giornale botanico italiano, 1990)
Abstract The xylem conduit dimensions (i.e. their width and length) have been measured in 1-year-old internodes, nodes and node-to-petiole (N-P) junctions of three species with diffuse-porous wood, namely Ceratonia siliqua L., Laurus nobilis L. and Olea europaea L. as well as of three species with ring-porous wood, namely Quercus ilex L., Q. suber L. and Q. pubescens Willd? The xylem conduit diameter and length distributions have been related to the drought resistance strategies adopted by the six species. C. siliqua and Q. ilex (drought avoiding water spenders) showed the widest xylem conduits (each species within its characteristic pattern of wood anatomy). This is consistent with their high demand of efficient water transport to leaves. L. nobilis (drought avoiding water saver) showed relatively narrow xylem conduits, efficient enough, however, to assure water supply to leaves at the reduced transpiration rate exhibited by the species. O. europaea, Q. suber and Q. pubescens (drought tolerants) showed the narrowest xylem conduits but also the longest ones. The xylem system of C. siliqua and Q. ilex represented a good compromise between efficiency and safety of the water transport, the former as due to wide xylem conduits, the latter to the reduced xylem conduit length as well as to the strong «hydraulic constrictions» at their nodes and N-P junctions. The ecological interpretation of such hydraulic architecture is discussed.
doi: 10.1080/11263509009430260